Symbiotic Efficiency of Arbuscular Mycorrhizal Fungi on the Growth Dynamics and Root Colonization of Waxy Corn (Zea mays L. var. ceratina) - Yuniyarti Hulu; Novri Youla Kandowangko; Muhammad Isra; Jusna Ahmad; Yuliana Retnowati; Aisyah Ahmad; Wirnangsih D. Uno; Hayatiningsih Gubali (Asosiasi Mikoriza Indonesia, 2026)
One of the important food crops in Gorontalo is corn (Zea mays L. var. ceratina), and root health is very important in determining its growth and productivity. This study aims to determine the root shoot-root ratio and root infection of waxy corn plants given arbuscular mycorrhizal fungi as biostimulants. This study was conducted from July to December 2025 using a completely randomized block design (RBD) with four different doses mycorrhizal arbuscular: 0, 10, 20, 30 g /polybag, which were replicated three times and observed periodically over 42 days after planting (DAP). The variables observed were root shoot-root ratio and root infection of plants at 14, 21, 28, 35, and 42 days after planting. The results showed that the application of mycorrhizae with different doses resulted in a root shoot ratio that increased in line with the increasing age of the plant. In contrast, it was interesting to find that in plant root infections, mycorrhizal application appeared to increase until the plants were 28 days after planting, after which it declined. This finding suggests that arbuscular mycorrhizal inoculation given to plants at different doses can impact root health, as indicated by the ratio of root decay to root infection. The symbiosis between mycorrhizae and plants is crucial for the growth of waxy corn.